A new species of Platycarpum (Rubiaceae, Henriquezieae) from Peruvian Amazon - Dávila, Nállarett; Kinoshita, Luiza Sumiko (Phytotaxa, 2016)
The new species Platycarpum loretensis (Rubiaceae) is endemic to the Loreto Department, Peru, and restricted to white sand forests (varillal), palm swamps, and peatlands. It is similar to P. orinocense from which can be separated by the oblanceolate leaves with prominulous intersecondary veins (vs. elliptic to ovate, without intersecondary veins), corollas 1.9–3 cm long (vs. 1.2–2(–2.2) cm long), and fruits 4.7–5.5 × 3.6–4.9 cm (vs. 3–3.5 × 2.8–3.5 cm).